Using Phonics system to develop pupils reading proficiency - Kamarundzaman, Noor Shana (2014)
This study investigates the effects of using phonics approach on pupils’ word attack and decoding skill, phonemic awareness and reading fluency. Besides that, it also examines teacher’s perception on using phonics approach for reading lesson. This study was carried out through quantitative and qualitative procedures. The quantitative procedure employed the quasi experimental design using pre-test posttest. For the qualitative procedure, a semi structured interview was carried out. The participants of this study were 28 Year 2 pupils and an English teacher from a primary school in Johor Bahru. Synthetic phonics approach was used in the study and the pupils were taught explicitly on how to make and blend the sounds. The pupils underwent four assessments in the pre-test and post-test. The results from the tests were analysed statistically. The study found that phonics approach increased pupils’ phonemics awareness but did not improve pupils’ word attack and decoding skill as well as pupils’ reading fluency. Moreover, the teacher viewed that phonics approach was confusing for the pupils. Besides that, it was noted that there was the interference of L1 during the lessons and assessments. It is suggested that for phonics approach to be effective in developing pupils’ reading proficiency, it should be conducted in small group of pupils